Dynamics of values in physical training scholarship of senior preschoolers under the influence of set of activities connected with physical scholarship optimization - Starchenko, A.U. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to consider changes of values in physical scholarship of senior preschoolers under the influence of experimental set of activities. Material: 117 children of preschool age took place in the experiment. Results : achieved actual changes in values of theoretical knowledge in physical culture. Integral indicator of theoretical knowledge of physical culture has improved by 52% and amounted to 20.5 points. Level of mastery of vital motor skills significantly altered, especially in the results of races - by 42% and jumps - 41%. After one uses means of children fitness there were marked significant improvements of basic values of vitally important skills and habits. Conclusions: set of held activities on optimization physical education proved its efficiency that makes it possible to recommend its use in preschool educational establishments.